1978
DOI: 10.1017/s0016756800041200
|View full text |Cite
|
Sign up to set email alerts
|

The Precambrian–Cambrian boundary problem: magnetostratigraphy of the Amadeus Basin, Central Australia

Abstract: A magnetostratigraphic study of Upper Proterozoic to early Cambrian sediments at 4 localities in Central Australia reveals the presence of a magnetic polarity pattern composed of 2 long quiet intervals, first of reversed then of normal polarity, which is then succeeded by a long mixed interval. Lithologic comparisons suggest that this pattern is a reflection of the behaviour of the geomagnetic field at that time, and probably is not a result of varying sedimentation rates. Two sampled sections in the Arumbera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(9 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The Cambrian thermal regime (Chumakov, 1984), confirmed by data on glauconite minerals, was similar to that of the Jurassic (Nikolaeva, 1981). According to these data, the temperature of seawater in Baltia was about 28 D C, and on the Siberian Platform and its Anabar-Sinsk Facies Region, about 30-38 D C. All the principal epicontinental basins were in low latitudes, as confirmed by paleomagnetic data obtained on fossiliferous sections in Australia, China, Mexico, and Mongolia, and on the East European and Siberian Platforms (Kirschvink, 1978;Khramov and Rodionov, 1980;Barr and Kirschvink, 1983;Zhang and Zhang, 1984;Kirschvink et 01., 1987). Therefore, the chief reason for increasing provincialism is, in our opinion, the fragmentation of the Paleopangea supercontinent (Kirschvink et 01., 1984).…”
Section: Discussionsupporting
confidence: 53%
“…The Cambrian thermal regime (Chumakov, 1984), confirmed by data on glauconite minerals, was similar to that of the Jurassic (Nikolaeva, 1981). According to these data, the temperature of seawater in Baltia was about 28 D C, and on the Siberian Platform and its Anabar-Sinsk Facies Region, about 30-38 D C. All the principal epicontinental basins were in low latitudes, as confirmed by paleomagnetic data obtained on fossiliferous sections in Australia, China, Mexico, and Mongolia, and on the East European and Siberian Platforms (Kirschvink, 1978;Khramov and Rodionov, 1980;Barr and Kirschvink, 1983;Zhang and Zhang, 1984;Kirschvink et 01., 1987). Therefore, the chief reason for increasing provincialism is, in our opinion, the fragmentation of the Paleopangea supercontinent (Kirschvink et 01., 1984).…”
Section: Discussionsupporting
confidence: 53%
“…Despite the limits of the present data, it seems worthwhile to attempt a comparison of these results with those reported for lower Cambrian sediments in the Amadeus and Georgina basins of Australia (Kirschvink, 1978;Burek, Walter & Wells, 1979). These authors found an interval of mixed polarity in Late Precambrian strata immediately beneath a widespread regional disconformity.…”
Section: C Comparison With the Lower Cambrian Of Australiamentioning
confidence: 70%
“…10). We make tentative interpretations of polarity here based upon previous paleomagnetic work that covers the post-Marinoan through Cambrian interval in the Amadeus basin (Kirschvink, 1978b), as well as previously published apparent polar wander (APW) paths for east Gondwana (e.g., Powell et al, 1993). According to these interpretations, the Earth's magnetic field in late Neoproterozoic time corre-sponds to reversed polarity for southwest and up directions and normal polarity for north-northeast and down directions; Australia thus is right-sideup near the equator, but mostly in the Northern Hemisphere (see Table 1 and Fig.…”
Section: Magnetostratigraphymentioning
confidence: 93%